A Qualitative Study of the Migration of Labourers and Factors Affecting their Well-Being in a Small Town (Leh) in North India - Mr. Ershad Hussain (International Journal of Indian Psychȯlogy, 2022)
Background: Migration is a process beginning with the migrants deciding to migrate, preparing themselves physically as well as mentally, and finally shifting themselves to the place of destination. Establishing themselves in a new environment with a different cultural, geographical and social setting is a challenging task mentally as well as emotionally and can have a significant impact on the wellbeing of the labourers. Aim & Objective: To explore the reason for migration, and factors affecting the well-being of migrant labourers. Methodology: A qualitative research design was adopted for data collection and interpretation. A sample of 10 migrant labourers was included who belonged to different districts of Bihar. The data collection methods included questionnaires, in-depth interviews, and a focus group discussion. Results: Major factors that affect the well-being were revealed to be at different levels for labourers ranging from accommodating themselves, finding work, payment for work, dealing with the harsh weather, dealing with work-related stress, physical health, socialization with others. Conclusion: Favourable and convenient situations in the factors yield favourable outcomes and contribute positively to the wellbeing of migrant labourers. While on the other hand, unfavourable situations related to these factors lead to unhealthy or negative physical, emotional, mental, and social outcomes. Therefore, negatively affecting their well-being